Apoptosis, Inflammatory Bowel Disease and Carcinogenesis: Overview of International and Greek Experience - Jannis Kountouras; Georgios Kouklakis; Christos Zavos; Dimitrios Chatzopoulos; John Moschos; Epaminodas Molyvas; Nikolaos Zavos (Canadian Journal of Gastroenterology)
Apoptosis is critical for organ development, tissue homeostasis, the elimination of abnormal cells and the maintenance of immune homeostasis by variable regulatory mechanisms. The death of T lymphocytes following their activation involves a series of proteases (caspases), which comprise the central executioners of apoptosis. Abnormal regulation of apoptosis results in disease. T-cell resistance against apoptosis contributes to inappropriate T-cell accumulation and the perpetuation of the chronic inflammatory process in inflammatory bowel disease with potential tumourigenic effect. The use of antitumour necrosis factor-alpha, anti-interleukin-6R and anti-interleukin-12 antibodies suppresses colitis activity by induction of T-cell apoptosis, thereby having important implications for the design of effective therapeutic strategies in inflammatory bowel diseases. Contrary to international data, the incidence of cancer in Greek patients with inflammatory bowel disease appears to be low. A balance between cell proliferation (Ki-67 overexpression) and apoptosis (Bax protein overexpression) may partly explain the low incidence of cancer development in Greek inflammatory bowel disease patients.